Who Guidelines on tularaemia (Editorial WHO World Health Organization, 2007)
Tularaemia is a bacterial zoonotic disease of the northern hemisphere. The bacterium is highly virulent for humans and a range of animals such us rodents, hares and rabbits. The present guidelines on tularaemia provide backgroud information on the disease, describe the curent best practice for its diagnosis and treatment in humans, sugest measures to be taken in case of epidemics and provide guidance on how handle f. rularensis in the laboratory, The target groups for these guidelines include clinicians, laboratory personnel, public health workers, vererinarians, and any other person with an interest in zoonoses.